A numerical investigation of the functionality of coronary bifurcation lesions with respect to lesion configuration and stenosis severity. Issue 12 (18th September 2015) - Pagiatakis, Catherine; Tardif, Jean-Claude; L'Allier, Philippe L.; Mongrain, Rosaire
Abstract The intervention of coronary bifurcation lesions is associated with higher rates of peri- and post-procedural clinical events compared to the treatment of isolated lesions. Overall, the factors that influence the dynamics of these types of configurations are still not well understood. A geometric multiscale model, consisting of a 3D representation of the left main coronary artery bifurcation and a 0D representation of the rest of the cardiovascular system, was developed. Computational fluid dynamics simulations of the 3D domain were executed by implementing the multiscale algorithm, in order to characterize the functionality of different multilesional configurations as a function of stenosis severity. The investigation found that coronary branch steal has a significant impact on the functionality of the disease and can render a two-lesion configuration more severe compared to a three-lesion configuration. As a result of the complexity of this phenomenon, it was also suggested that certain lesion configurations could result in false negatives in diagnosis when employing a pullback pressure recording across the tandem lesions. In conclusion, this study showed that coronary bifurcation lesions are subject to intricate haemodynamic interactions which render the characterization of their functionality complex and could have significant clinical implications with regards to their diagnosis and prognosis.